Jan Smuts and the Bulhoek Massacre: Race and state violence in the making of South Africa, 1919-1920s - Bongani Ngqulunga (Contree, 2022)
The purpose of this article is to examine the role played by General JC Smuts, the prime minister of the Union of South Africa at the time, in the incident known as the Bulhoek Massacre which took place in May 1921. The discussion locates the Bulhoek incident in the broader context of Smuts’s attitude towards black people in South Africa. It explores his ideas and views on the subject of race, and scrutinises the policies that the government introduced under his premiership. It shows how he steered the country towards shoring up minority government and the political and economic exclusion, marginalisation and domination of African people in South Africa. In this it follows on the works of many other historians who have written in this vein and contend that the Bulhoek Massacre is the exemplar of Smuts’s views on the matter of race in South Africa.